2018
DOI: 10.1128/iai.00542-18
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 + T Regulatory Cells as a Potential Target for Immunotherapy against Primary Infection with Echinococcus multilocularis Eggs

Abstract: Alveolar echinococcosis (AE) is a lethal disease caused by infection with the metacestode stage of the helminth Echinococcus multilocularis, which develops into a tumorlike mass in susceptible intermediate hosts. The growth potential of this parasite stage is directly linked to the nature of the surrounding periparasitic immune-mediated processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…infection, SAE) not only when Foxp3 + Tregs were depleted preventively before E. multilocularis infection, but also when they were depleted therapeutically when the infection was already established (oral infection, PAE) . The significantly smaller average lesion size in the liver due to Foxp3 + Tregs depletion in PAE was associated with a higher Th1 immune response, a lower IL‐10 production and upregulation of APC activation . The late infection of both SAE and PAE was characterized by a strong Foxp3 expression and weak expression of most mediators, suggesting that their production is suppressed by Tregs .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…infection, SAE) not only when Foxp3 + Tregs were depleted preventively before E. multilocularis infection, but also when they were depleted therapeutically when the infection was already established (oral infection, PAE) . The significantly smaller average lesion size in the liver due to Foxp3 + Tregs depletion in PAE was associated with a higher Th1 immune response, a lower IL‐10 production and upregulation of APC activation . The late infection of both SAE and PAE was characterized by a strong Foxp3 expression and weak expression of most mediators, suggesting that their production is suppressed by Tregs .…”
Section: Discussionmentioning
confidence: 98%
“…With inducible depletion of Foxp3 + Tregs, the metacestode growth yielded a significantly lower parasite load (i.p. infection, SAE) not only when Foxp3 + Tregs were depleted preventively before E. multilocularis infection, but also when they were depleted therapeutically when the infection was already established (oral infection, PAE) . The significantly smaller average lesion size in the liver due to Foxp3 + Tregs depletion in PAE was associated with a higher Th1 immune response, a lower IL‐10 production and upregulation of APC activation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During echinococcosis, the impaired host immune response is paralleled by an increased expression of TGF-β signaling components in periparasitic host cells and tissues [10,11,16,24–27] with the expansion of tolerogenic CD4 + CD25 + Foxp3 + Treg cells [6,15,2830]. Echinococcus antigens can stimulate the expression of CD25 by CD4 + T helper cells from AE infected patients, contributing to the differentiation into Treg [31].…”
Section: Introductionmentioning
confidence: 99%
“…This group also found Foxp3 gene expression to be elevated in these cells and a higher frequency of CD4 + CD25 + Foxp3 + Treg cells in the peritoneum and the spleen of E. multilocularis -infected mice [15,28]. Subsequent studies then convincingly revealed Foxp3+ Treg as key players in the immunoregulatory processes that facilitate the establishment and persistence of E. multilocularis metacestode in their mammalian hosts [2830]. Consistent with such observations, our previous report of the ability of E. multilocularis metacestode E/S products to expand host Treg in vitro [6], ultimately suggested that Treg expansion during AE, as increasingly reported in the literature, could go beyond a simple homeostatic balancing mechanism.…”
Section: Introductionmentioning
confidence: 99%